Pemetaan Tipe Iklim Oldeman Tahun 2022-2100 Berdasarkan Skenario SSP5-8.5 Model ACCESS-CM2 - Aqasha Raechan Anam; Cakra, Alif Putra; Wardoyo, Wildan Auliya Azka; Asary, Sopia Mince; Virgianto, Rista Hernandi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
Climate change is part of the most serious problem for the life of the world community today. One sector that is highly vulnerable to the impacts of climate change is the agricultural sector. One method that can be used is to see a picture of the future climate by making climate projections based on certain scenarios. The data used in this study are monthly rainfall data at 4 observation points of BMKG stations as well as Historical and Projection model data from the SSP5-8.5 ACCES-CM2 model scenario at 36 points in the West Java region taken from Copernicus ECMWF at https://cds.climate.copernicus.eu/. The results showed that a comparison of Oldeman's classification based on the 2 projection data used showed differences, namely for SSP2-4.5 data it was more categorical in class D while for SSP5-8.5 data the classification was in class C except for the period 2071-2100 for SSP2-4.5 data showing classification in class B. It can be said that in the West Java region rice can be planted once based on SSP2-4.5 data and twice based on SSP5-8.5 data.